Pediatric heart transplantation across a positive crossmatch: First year results from the CTOTC‐04 multi‐institutional study. Issue 9 (28th May 2018) - Webber, S.; Zeevi, A.; Mason, K.; Addonizio, L.; Blume, E.; Dipchand, A.; Shaddy, R.; Feingold, B.; Canter, C.; Hsu, D.; Mahle, W.; Armstrong, B.; et al.
Abstract : Sensitization is common in pediatric heart transplant candidates and waitlist mortality is high. Transplantation across a positive crossmatch may reduce wait time, but is considered high risk. We prospectively recruited consecutive candidates at eight North American centers. At transplantation, subjects were categorized as nonsensitized or sensitized (presence of ≥1 HLA antibody with MFI ≥1000 using single antigen beads). Sensitized subjects were further classified as complement‐dependent cytotoxicity crossmatch (CDC‐crossmatch) positive or negative and as donor‐specific antibodies (DSA) positive or negative. Immunosuppression was standardized. CDC‐crossmatch–positive subjects also received perioperative antibody removal, maintenance corticosteroids, and intravenous immunoglobulin. The primary endpoint was the 1 year incidence rate of a composite of death, retransplantation, or rejection with hemodynamic compromise. 317 subjects were screened, 290 enrolled and 240 transplanted (51 with pretransplant DSA, 11 with positive CDC‐crossmatch). The incidence rates of the primary endpoint did not differ statistically between groups; nonsensitized 6.7% (CI: 2.7%, 13.3%), sensitized crossmatch positive 18.2% (CI: 2.3%, 51.8%), sensitized crossmatch negative 10.7% (CI: 5.7%, 18.0%), P  = .2354. The primary endpoint also did not differ by DSA status. Freedom from antibody‐mediated and cellular rejection was lower in the crossmatch positive group and/or in the presence of DSA. Follow‐up will determine if acceptable outcomes can be achieved long‐term. Abstract : Transplantation across a positive crossmatch is associated with low risk of death or graft loss/rejection with hemodynamic compromise, but with high rates of antibody‐mediated rejection. See the other CTOTC articles onpages 2135 and2163, and the editorial onpage 2107 .